Mitigasi Bencana Gunung Merapi Berbasis Desa Bersaudara (Sister Village) di Kecamatan Musuk Kabupaten Boyolali Jawa Tengah - Astriani, Fiqih, Dr. Ir. Imam Hardjono, M.Si (2017)
The purpose of this study is to provide information and recommendations for the prone villages in the determination of reciever villages and to study the response of the prone villages and the receiver candidate villages (the safe village) if sister village applied as disaster mitigation program in district Musuk Boyolali Regency. The method of this research is survey method to findout the condition of the research area directly, while the methods of retrieval data is using census data in the form of population and live stock for prone villages and the facilitiy data and the capacity of the shelter safe villages. The analysis of the research result is using quantitative analysis by calculating and comparing the number of refugees and evacuation capacity. Based on the research results, prone villages in district Musuk are Cluntang, Lanjaran, Mriyan and Sangup can pair with some villages in Boyolali district and previously have become accustomed to receive refugee, i.e.,Village Kemiri,Village Kebonbimo, Village Siswodipuran, Village Pulisen, village Mudal, village Kiringan, village Penggung and village Banaran. The recommended results i.e. Village Cluntang with village Lanjaran, village Penggung with village Pulisen, village Mriyan with village Kemiri and village Siswodipuran with village Sangup. The response of the vulnerable villages to the programs application by sister village is village Cluntang, Lanjaran and Mriyan are willing to implement this program, while the village Sangup refused. The response of safe villages candidate is all the villages are willing to carryout the program of sister village.